Impedance source inverters with enhanced voltage boost capability - Mo, Wei (2014)
Semiconductor-based power inverters have widely been used in the industry because of their compact size, high power density and efficiency. However, traditional power inverters can only either step down or up their outputs, but not both. They are hence not suitable for interfacing renewable energy sources to the main power grid. The reason is linked to the inconsistent and high weather dependent nature of the renewable sources, which would then require buck-boost energy conversion for maximum flexibility. To achieve buck-boost capabilities, a front-end dc-dc converter is usually added to a rear-end dc-ac inverter. Alternatively, single-stage buck-boost inverters can also be used, which comparatively, are more integrated. A few single-stage buck-boost topologies have so far been reported. They include the Ćuk and SEPIC-derived inverters, which in effect, are nice integrations of the Ćuk and SEPIC dc-dc converters to the rear-end dc-ac inverters. Other possibilities are the Z-source inverters, which over the years, have attracted more attention than the others because of their many unique advantages. For example, the added X-shaped impedance network of the Z-source inverters allows two switches from the same phase-leg to turn on without causing damages. The shoot-through state is instead intentionally added for voltage boosting, while retaining the usual voltage-buck capability of the six-switch inverter bridge. Besides two-level Z-source inverters, three-level Z-source NPC inverters have also been studied, whose main intention is to lower the switch voltage stress, while improving the inverter output waveform quality. Even with their proven advantages, existing Z-source inverters still have some shortcomings to resolve. One of them is their chopped input current, which requires bulky input passive filter for smoothing their input current. This can be resolved by the embedded Z-source, quasi-Z-source and LCCT inverters, whose common objective is to make the input current continuous by using an existing Z-source inductor. Another shortcoming is related to the low modulation ratio permitted, while performing high voltage boosting with high shoot-through duty ratio. The low modulation ratio then causes the inverter waveform quality to drop and the switch voltage stress to rise. These effects are no doubt undesirable, leading to a few topologies being proposed to resolve them. One solution is to use coupled inductors or transformer, leading to the development of trans-Z-source inverter, T-source inverter and trans-quasi-Z-source inverter. These inverters offer a high voltage gain at a high modulation ratio, which needless to say, have resolved the complications mentioned earlier regarding waveform quality and switch voltage stress. They however still draw a chopping input current, which at times, might not be tolerated by the source. Therefore, the intention set for this thesis is to formulate a few topologies with enhanced voltage boost, while drawing continuous input current. The proposed inverters use one coupled transformer, one inductor and two capacitors, which are more than components used by the trans-Z-source inverters. The components used are however the same if a low-pass filter is included with the latter for input current filtering. The component selection process, voltage/current stress and efficiency comparison between the proposed inverters and traditional impedance-source inverters will all be covered in the thesis. Simulation and experimental results will also be given for verifying the theoretical analyses presented. To further reduce the device switching stress and improve the output waveform quality, a series of impedance-source NPC inverters based on transformer-capacitor impedance network inserted to the front-end of the NPC inverter bridge are proposed. These inverters integrate all advantages of the transformer-based impedance-source two-level inverters and classical NPC three-level switching. The proposed trans-Z-source NPC inverter has enhanced voltage boost capability over the traditional Z-source NPC inverters. The proposed gamma-source NPC inverter, on the other hand, uses a transformer with a smaller turns ratio to gain the same voltage boost capability as that of the trans-Z-source NPC inverter. The third type of transformer-capacitor impedance-source NPC inverter further extends the concepts of asymmetrical embedded Z-source inverter to the NPC configuration. The result is again an enhanced voltage boost similar to those of the first two types of transformer-capacitor impedance-source inverters. The third type of NPC inverter however draws a continuous input current, which is different from the chopping discontinuous input current drawn by the earlier two types of transformer-capacitor impedance-source NPC inverters. All topologies and concepts discussed so far have appropriately been verified in experiments, whose results are explained in relevant chapters. Last but not least, a model predictive control method has been adapted for controlling the traditional Z-source inverters and also the proposed inverters for use in renewable energy systems that require buck-boost energy conversion. The discussed method has been tried in simulation with promising results observed.